2017
DOI: 10.3233/blc-170107
|View full text |Cite
|
Sign up to set email alerts
|

Use of Adjuvant Chemotherapy in Patients with Advanced Bladder Cancer after Neoadjuvant Chemotherapy

Abstract: Objectives:To compare the outcomes of adjuvant chemotherapy (AC) versus observation in patients with non-organ confined disease after neoadjuvant chemotherapy and radical cystectomy (RC).Materials and methods:Using the National Cancer Database, we identified patients who received NAC prior to RC and had advanced stage (pT3/4) or pathologically involved nodes (pN+) at the time of surgery from 2004–2013. We determined whether patients then received AC or were managed with observation only and used multivariable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Moreover, patients treated with adjuvant chemotherapy were excluded from this study, suggesting that we do not know the role of adjuvant radiotherapy in patients in addition to adjuvant concurrent/sequential chemotherapy. While this study was not designed to determine the efficacy of adjuvant chemotherapy after neoadjuvant chemotherapy and cystectomy, there may be potential benefits for high risk patients [ 28, 29 ]; additional research is needed to further explore this question. Overall, these limitations do not diminish the need for further investigations of the role of adjuvant therapy for LABC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients treated with adjuvant chemotherapy were excluded from this study, suggesting that we do not know the role of adjuvant radiotherapy in patients in addition to adjuvant concurrent/sequential chemotherapy. While this study was not designed to determine the efficacy of adjuvant chemotherapy after neoadjuvant chemotherapy and cystectomy, there may be potential benefits for high risk patients [ 28, 29 ]; additional research is needed to further explore this question. Overall, these limitations do not diminish the need for further investigations of the role of adjuvant therapy for LABC.…”
Section: Discussionmentioning
confidence: 99%
“…The data for adjuvant chemotherapy after NAC + RC are not clear. A recent study of 705 patients found that those with non‐organ‐confined bladder cancer (pT3/pT4) at time of RC or node‐positive disease at time of RC, who received NAC, had no benefit to adjuvant chemotherapy . Currently, National Comprehensive Cancer Network recommendations for adjuvant treatment are for patients with pT3‐pT4 disease or nodal disease .…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging research focused on improved patient selection for cisplatin‐based NAC via the use of tumour subtyping, genomics and biomarkers . Such strategies might not only enhance the benefit of NAC but also avoid undue harm or futility of NAC, especially in those who are likely to be non‐responders .…”
Section: Discussionmentioning
confidence: 99%
“…The use of AC after cisplatin-based NAC is not recommended, given conflicting results from observational series and lack of prospective data [30,[149][150][151][152][153][154]. Biologically, it is presumed tumor cells resistant to cisplatin-based NAC will also be refractory to AC.…”
Section: Adjuvant Chemotherapy (Ac)mentioning
confidence: 99%